2012
DOI: 10.1159/000342618
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Adequate Predialyis Care and Previous Hemodialysis, but Not Hemoglobin Variability, Are Independent Predictors of Anemia-Associated Mortality in Incident Brazilian Peritoneal Dialysis Patients: Results from the BRAZPD Study

Abstract: Background/Aims: The objective of this study was to analyze the prevalence of anemia and variability of hemoglobin (Hb) values in peritoneal dialysis (PD) patients, to establish its associated factors and their impact on clinical outcomes in a large cohort of patients starting PD treatment. Methods: Data were collected monthly in incident patients, who were followed until the primary endpoint (death from all causes) or until leaving the study. Results: 2,156 patients starting PD were included. The prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2014
2014
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
1
0
2
Order By: Relevance
“…In one large Chinese study, among independent risk factors of mortality in CAPD patients with diabetes were lower hemoglobin (HR 0.978, 95% CI 0.964 – 0.992, p = 0.003) and lower serum albumin (HR 0.924, 95% CI 0.876 – 0.976, p = 0.004) at initiation of CAPD (21). Also, the BRAZPD study, a large cohort of PD patients in Brazil, reported anemia (hemoglobin [Hb] < 11 g/dl) to be present in 57% of CAPD patients at baseline and to be an independent predictor of mortality (22). Although an attempt is often made for all CAPD patients treated at the PKDC unit in Limpopo to receive adequate anemia treatment according to guidelines, the role of nutritional status in these patients, which was not assessed in this study, could have contributed to anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In one large Chinese study, among independent risk factors of mortality in CAPD patients with diabetes were lower hemoglobin (HR 0.978, 95% CI 0.964 – 0.992, p = 0.003) and lower serum albumin (HR 0.924, 95% CI 0.876 – 0.976, p = 0.004) at initiation of CAPD (21). Also, the BRAZPD study, a large cohort of PD patients in Brazil, reported anemia (hemoglobin [Hb] < 11 g/dl) to be present in 57% of CAPD patients at baseline and to be an independent predictor of mortality (22). Although an attempt is often made for all CAPD patients treated at the PKDC unit in Limpopo to receive adequate anemia treatment according to guidelines, the role of nutritional status in these patients, which was not assessed in this study, could have contributed to anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudos corroboram com esses achados (DE MORAES et al, 2014;OLIVEIRA et al, 2014;RAJAEEFARD et al, 2016;VAVRUK et al 2012, GONÇALVES et al, 2013 .…”
Section: Discussionunclassified
“…Esse dado é semelhante em vários estudos (BAE et al, 2015;GONÇALVES et al, 2013;OLIVEIRA et al, 2014;SANABRIA et al, 2015). Ao analisarmos a média Ainda Bevilacqua et al (1995) descreveu dados referentes ao tempo de acompanhamento inferior ao deste estudo como também, Oliveira et al (2016) no qual o tempo de acompanhamento foi de 1,5 anos de seguimento.…”
Section: Discussionunclassified